National intelligence and science beyond the great divide in analysis and policy - Agrell, Wilhelm author; Treverton, Gregory F. (Oxford University Press, 2015)
Intelligence and science are both facing increasing demands for answers that neither can or should provide, at least not in the way policymakers and public opinion often expect. The twentieth-century's defined and knowable threats are gone. This book is one of the first books to outline this change and its profound implications. The time has come not to bridge this divide, but instead to move beyond it to develop new forms for discovering, understanding, and reactingto the emerging challenges of a globalized yet fragmenting world.